The severity of temporomandibular joint disorder by teeth loss in the elderly - Herdiyani, Indry; Kurnikasari, Erna; Damayanti, Lisda (Universitas Padjadjaran, 2011)
Temporomandibular joint dysfunction is a term that covers a number of clinical problems that involves masticatory muscles, temporomandibular joints, and related structures, or both. Loss of tooth was an etiology of temporomandibular joint dysfunction. The purpose of this study was to obtain the description of temporomandibular joint dysfunction level that caused by tooth loss of elderly in three nursing home Bandung. This was a descriptive study using the survey method of the elderly in three nursing home Bandung. A total of 34 people consist 6 males and 28 females. The subjects were examined by symptoms of temporomandibular joint dysfunction and the dysfunction level was assessed by Helkimo Clinical Dysfunction Index. The result of this study shows that elderly in Nursing Home Bandung have mild dysfunction level was 7 (14.71%), moderate dysfunction level was 22 (64.71%), and severe dysfunction level is 5 (20.58%). It can be concluded that loss of the teeth is one of the etiologies of temporomandibular joint disorder. Based on the research conducted, it can be concluded that all elderly with teeth loss will have the temporomandibular joint disorder and the most severity happens based on teeth loss by using the Helkimo Clinical Disfunction Index score was the moderate disorder.